Performance of a double-junction solar cell under various environmental conditions - I. D. SARA (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2014)
PV manufacturers only provide performance of a PV technology at a standard test condition (STC) where the irradiance at 1000 W/m2, spectrum of AM1.5 and a module temperature at 25°C. This information is inadequate to represent the performance of the PV device under real operating conditions. This paper investigates the performance of a double-junction solar cell under different climatic conditions, i.e. temperature, irradiance, solar spectrum, and the angle of incidence. The effects of environmental conditions on the cell’s performance are observed by simulating their current and voltage characteristics using a one-diode. The results show that the short-circuit current of a double-junction device is spectrally sensitive to the incident irradiance and solar spectrum. When the angle of incidence is greater than 60°, the maximum power of a double-junction solar cell reduces significantly